The Developmental Case for BRICS - Anderson, Tim; Yulianti, Dina (Institute of International Studies, 2023)
This paper argues the developmental case for Indo-Pacific and Global South nations joining BRICS Plus, which presents the best possibilities to escape the dictatorship of the dollar, whether through bilateral swaps, new baskets of currencies or some new shared digital forms of exchange. This move is necessary for two main reasons. First, the dollar dictatorship has damaged and continues to damage developing countries through depreciation of non-dollar currencies, adverse income effects and associated damaging impact on credit ratings and investment. Second, the expanded use of unilateral US and EU “sanctions” (unilateral coercive measures) imposes crippling siege warfare on more than 20 nations while seriously damaging the free trade options of third party nations. That siege warfare and its effects is only possible because of the tight nexus between the dollar, the US-dominated SWIFT system and the US capture of protocol agreements such as those against money laundering and the financing of terrorism. Establishing alternative financial mechanisms to the dollar dictatorship has become essential to the developmental possibilities of Global South economies in Asia, Africa and Latin America, and the weight and determination of the BRICS Plus group presents the best chance to build such alternatives.